Histone methyltransferase SETDB1 contributes to melanoma tumorigenesis and serves as a new potential therapeutic target. Issue 12 (9th June 2019) - Orouji, Elias; Federico, Aniello; Larribère, Lionel; Novak, Daniel; Lipka, Daniel B.; Assenov, Yassen; Sachindra, Sachindra; Hüser, Laura; Granados, Karol; Gebhardt, Christoffer; Plass, Christoph; Umansky, Viktor; et al.
Abstract : Alterations in histone modifications play a crucial role in the progression of various types of cancer. The histone methyltransferase SETDB1 catalyzes the addition of methyl groups to histone H3 at lysine 9. Here, we describe how overexpression of SETDB1 contributes to melanoma tumorigenesis. SETDB1 is highly amplified in melanoma cells and in the patient tumors. Increased expression of SETDB1, which correlates with SETDB1 amplification, is associated with a more aggressive phenotype in in vitro and in vivo studies. Mechanistically, SETDB1 implements its effects via regulation of thrombospondin 1, and the SET‐domain of SETDB1 is essential for the maintenance of its tumorigenic activity. Inhibition of SETDB1 reduces cell growth in melanomas resistant to targeted treatments. Our results indicate that SETDB1 is a major driver of melanoma development and may serve as a potential future target for the treatment of this disease. Abstract : What's new? Alterations in histone modifications play a crucial role in the progression of various types of cancer. The histone methyltransferase SETDB1 is known to be involved in malignant melanoma. However, little is known about its effects or mechanisms of action in humans. In this study, the authors found that increased SETDB1 expression is linked to poor prognosis in melanoma patients, and that SETDB1 regulates expression of the oncogene THBS1. They also found that inhibiting SETDB1 leads to a strong reduction in melanoma‐cell viability. This enzyme may thus offer a novel therapeutic target.